2022
DOI: 10.3389/fspor.2022.841653
|View full text |Cite
|
Sign up to set email alerts
|

From Policy to Practice: Measures Against Sexual Abuse by Swedish Sports Federations

Abstract: The sport movement must protect children and young athletes from all forms of abuse. However, research points to a disconnect between policy and implementation of policy against sexual abuse. No studies have investigated measures against sexual abuse in Swedish sport. The purpose of this study was to explore measures against sexual abuse in the 10 largest sports federations (SFs) for child and youth sport in Sweden. The study draws on interviews with representatives (n = 18) of the SFs and on a review of SFs' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Sport managers also need to be better equipped to recognize signs and symptoms of IV in sport ( 32 ). Although training is perceived as one of the most important elements for the prevention of IV in sport, it is also one of the greatest challenges in terms of organizational capacity ( 43 , 44 ). In addition, sport managers recommended having an independent body to monitor, investigate and manage complaints.…”
Section: Resultsmentioning
confidence: 99%
“…Sport managers also need to be better equipped to recognize signs and symptoms of IV in sport ( 32 ). Although training is perceived as one of the most important elements for the prevention of IV in sport, it is also one of the greatest challenges in terms of organizational capacity ( 43 , 44 ). In addition, sport managers recommended having an independent body to monitor, investigate and manage complaints.…”
Section: Resultsmentioning
confidence: 99%
“…Sporting organizations have indicated that because CSA is not as common as other forms of abuse in sport, it is not worthy of their attention, although they agree it is unacceptable and are aware of the detrimental effects of CSA (Johansson, 2022). Furthermore, these sporting organizations reported a culture of silence around CSA (Johansson, 2022). The tolerance of CSA incidents, a culture of silence, and the failure to implement and regulate CSA policy is disadvantageous to the eradication of CSA in sport.…”
Section: Discussionmentioning
confidence: 99%
“…and regulation of CSA policy and procedures, has been reported as a reason why preventive programs for CSA in sport may be ineffective (Milroy et al, 2022;Owusu-Sekyere et al, 2022;Roberts et al, 2020). Sporting organizations have indicated that because CSA is not as common as other forms of abuse in sport, it is not worthy of their attention, although they agree it is unacceptable and are aware of the detrimental effects of CSA (Johansson, 2022). Furthermore, these sporting organizations reported a culture of silence around CSA (Johansson, 2022).…”
Section: Enabling Factorsmentioning
confidence: 99%
See 1 more Smart Citation